57 Exploring the functions of an E-prescribing system to reduce prescribing errors and improve inpatient medication record keeping. (3rd November 2019) - Sim, Nicholas Keyi; Walter, Talia; Pickin, Sally; Stanger, Sophie; Tanqueray, Eleanor; Sperrin, Justin; Subramaniam, Nadisha; Mullins, Sophie; Rusby, Polly; Atton, Giles; Isaac, Thomas; Royan, David; et al.
Abstract : The e-prescribing system at the Great Western Hospital offers a note taking system that pharmacy uses to record a 24-hour drug history and allows users to add notes clarifying any changes. A QI project aimed to reduce near-misses caused by prescribing errors by increasing the utilisation of the 24-hour drug history and note system. This was done via education targeted at the primary users of the system using pre-existing channels in the trust. Three cycles of interventions were implemented: teaching the prescribers how to use the system during teaching sessions, increasing publicity via posters in clinical areas and trust mailing lists, and making a version of the guide available on the trust intranet. The primary measure was the number of near-misses identified from pharmacy phone calls to the medical team in a 24-hour period, which fell from 22 to 10 to 8 to 7. Secondary measures were the percentage drug histories being 'read', which improved from 12.77% to 23.26% initially but fell to 2.38% and 4.65%; and the percentages of drug charts with notes clarifying discrepancies which changed little despite intervention from 18.92% to 28.00% to 33.33% to 29.54%. The interventions show that it is possible to use existing trust education channels to produce a sustainable reduction in near-misses. The reduction in percentage drug histories being 'read', and the lack of change in the percentages of drug charts with notes clarifying discrepancies illustrate the challenges in using an e-prescribing system.